CX3CR1 knockout aggravates Coxsackievirus B3-induced myocarditis. - Irene Müller; Kathleen Pappritz; Konstantinos Savvatis; Kerstin Puhl; Fengquan Dong; Muhammad El-Shafeey; Nazha Hamdani; Isabell Hamann; Michel Noutsias; Carmen Infante-Duarte; Wolfgang A Linke; Sophie Van Linthout; et al. (PLoS ONE)
Studies on inflammatory disorders elucidated the pivotal role of the CX3CL1/CX3CR1 axis with respect to the pathophysiology and diseases progression. Coxsackievirus B3 (CVB3)-induced myocarditis is associated with severe cardiac inflammation, which may progress to heart failure. We therefore investigated the influence of CX3CR1 ablation in the model of acute myocarditis, which was induced by inoculation with 5x105 plaque forming units of CVB3 (Nancy strain) in either CX3CR1-/- or C57BL6/j (WT) mice. Seven days after infection, myocardial inflammation, remodeling, and titin expression and phosphorylation were examined by immunohistochemistry, real-time PCR and Pro-Q diamond stain. Cardiac function was assessed by tip catheter. Compared to WT CVB3 mice, CX3CR1-/- CVB3 mice exhibited enhanced left ventricular expression of inflammatory cytokines and chemokines, which was associated with an increase of immune cell infiltration/presence. This shift towards a pro-inflammatory immune response further resulted in increased cardiac fibrosis and cardiomyocyte apoptosis, which was reflected by an impaired cardiac function in CX3CR1-/- CVB3 compared to WT CVB3 mice. These findings demonstrate a cardioprotective role of CX3CR1 in CVB3-infected mice and indicate the relevance of the CX3CL1/CX3CR1 system in CVB3-induced myocarditis.